Reinterpretasi Hadis Tentang Peran Perempuan Sebagai Pendidik Dalam Keluarga Dan Masyarakat Modern - Khairil Ikhsan Siregar; Mila Hanifah (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
The role of women in family and community education has a strong foundation in Islamic teachings, particularly through the Prophet’s hadiths. However, the interpretation of these hadiths is often still bound by past social and cultural contexts that are less relevant to the dynamics of modern life. This article uses a hermeneutic and contextual approach to reinterpret a number of hadiths related to the role of women as educators. This research is qualitative, employing content analysis of selected hadiths found in Ṣaḥīḥ al-Bukhārī, Ṣaḥīḥ Muslim, Sunan Abī Dāwūd, al-Tirmidhī, al-Nasā’ī, and Ibn Mājah. The study shows that these hadiths contain adaptable meanings in response to contemporary needs and affirm the position of women as active agents in education, both within the family and in society. This reinterpretation is expected to contribute to Islamic discourse responsive to contemporary gender and educational issues.